2019
DOI: 10.5830/cvja-2018-063
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary or intravenous abciximab after aspiration thrombectomy in patients with STEMI undergoing primary percutaneous coronary intervention

Abstract: Objectives: To test whether aspiration thrombectomy with intracoronary (IC) instead of intravenous (IV) administration of abciximab could reduce the no-reflow phenomenon in patients undergoing primary percutaneous intervention (PCI) for ST-elevation myocardial infarction (STEMI). Background: Despite recanalisation with PCI, failure to restore microvascular flow may affect the prognosis of patients with STEMI. A combination of aspiration thrombectomy with IC abciximab may improve distal perfusion. Methods: Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Two recent randomized clinical trials found a similarity between IC and IV abciximab in post-procedural TMI flow grade 3 supporting our finding [15,16]. However, another study realized more myocardial infarction patients experienced TIMI flow grade 3 in IC abciximab but the results were not statistically significant [23].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Two recent randomized clinical trials found a similarity between IC and IV abciximab in post-procedural TMI flow grade 3 supporting our finding [15,16]. However, another study realized more myocardial infarction patients experienced TIMI flow grade 3 in IC abciximab but the results were not statistically significant [23].…”
Section: Discussionsupporting
confidence: 84%
“…A total of 15 randomized controlled trials (RCTs) met our inclusion criteria [5][6][7][8][9][10][15][16][17][18][19][20][21][22][23] . The included studies compared intracoronary versus intravenous abciximab in myocardial infarction after percutaneous coronary intervention.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of clinical results, patients with acute coronary syndrome have presented with a significant reduction in infarct size [ 274 ]. In addition, intracoronary administration combined with thrombectomy significantly reduced infarct size [ 275 ]. The application of novel therapies in clinical practice is challenging, and there is an extensive list of not favorable outcomes in I-R treatments in clinical trials.…”
Section: Alternative Interventions In Clinical Trialsmentioning
confidence: 99%
“…105 Abciximab is indicated for use in patients undergoing primary percutaneous coronary intervention and myocardial ischemia, together with heparin and acetylsalicylic acid. 106 Side effects of abciximab use are thrombocytopenia, bleeding, abdominal pain, nausea and vomiting. 107 Currently, abciximab is in shortage, as listed by the FDA, because of an interruption in manufacturing at a third-party site.…”
Section: Ornatin Ementioning
confidence: 99%